Monoclonal antibody specific for Listeria monocytogenes, Listeria innocua, and Listeria welshimeri. - Siragusa, G R (1990)
Eight hundred fifty-nine murine hybridomas were produced from eight fusions, and 27 were characterized for secretion of antibodies reactive to Listeria monocytogenes. One monoclonal antibody (MAb), P5C9, reacted with all test strains of L. monocytogenes (31 of 31), L. innocua (3 of 3), and L. welshimeri (1 of 1) but not with any strains of the other four Listeria species or with any of 22 gram-positive or 11 gram-negative species of bacteria when tested in microtiter and dot blot enzyme immunoassays. Of the other 26 antibodies, 20 reacted with either L. monocytogenes Scott A or V7 and with some or all of the other six Listeria species but also cross-reacted with some or all of the non-Listeria bacteria tested. MAb P5C9 is of the immunoglobulin G1 murine subclass. In Western blot (immunoblot) analyses, this MAb reacted with a single antigen with a molecular weight of 18,500, and it is shared in common with all three reactive species, L. monocytogenes, L. innocua, and L. welshimeri. This antigen was extracted with detergent and appeared to be cell bound.